PENGARUH GAYA KEPEMIMPINAN DAN KEPUASAN KERJA TERHADAP KINERJA GURU SERTA DAMPAKNYA DALAM PENGAMBILAN KEPUTUSAN DI SMA DAN SMK MUHAMMADIYAH KOTA PALEMBANG - Fauzi, Taty; Andriani, Yulia; Hendro, Omar (MOTIVASI, 2020)
ABSTRACTPurpose - This study aims to determine and analyze, 1). The influence of leadership style on teacher performance. 2). Effect of satisfaction on teacher performance. 3). The influence of leadership style has an impact on decision making. 4). The effect of job satisfaction has an impact on decision making at the Muhammadiyah High School and Vocational School in Palembang, and 5). The effect of teacher performance has an impact on decision making.Design/methodology - The design of this research is associative research by connecting between variables. The data used in this study were primary and secondary data, and respondents' answers were 80 teachers in the Muhammadiyah High School and SMK Palembang City. The analytical method used is path analysis and through testing the validity and reliability. Test data used to determine the characteristics of the data are the normality test and linearity test. The test model used consisted of multicollinity test and heterodecacity test.Findings - 1). Teacher leadership style and job satisfaction significantly influence teacher performance. 2). Leadership style and job satisfaction have an impact on decision making. 5). Teacher performance has an impact on decision making in the Muhammadiyah High School and SMK Palembang City. Implications: This study provides results that motivation and competence are supporting factors for improving employee performance.Keywords : Leadership Style, Job Satisfaction, Performance and Decision Making.